Estrategia didáctica para el desarrollo de la motricidad gruesa en los estudiantes del nivel básico en la Unidad Educativa José María Estrada Coello, Cantón Babahoyo - Robledo Lozano, Jossie Esteban (2025)
This study addresses a critical issue in the educational field, specifically at the José María Estrada Coello Educational Unit in Babahoyo, Ecuador. In an environment where the number of sedentary children and adolescents has reached alarming levels, the lack of development of motor skills is noticeable, affecting not only their physical capacity but also their academic and social performance. This situation necessitates an in-depth analysis of teaching strategies that can be used to improve student motivation, which is essential for their overall development. The objective of this research is to determine and examine the most effective pedagogical strategies for promoting gross motor skills in elementary school students. The question to be answered is: What teaching strategies enable students in this school to develop gross motor skills? Using a blended learning approach, the effectiveness of various physical and creative activities that not only promote physical activity but also enhance the overall educational experience will be evaluated. This study focuses on the importance of gross motor skills for students' physical, emotional, and social well-being. In addition to encouraging their participation in recreational and sports activities, the development of adequate gross motor skills also improves their safety and quality of life. In the absence of structured programs in the curriculum that address this issue, a set of activities is proposed that, through appropriate teaching strategies, enable students to understand and use these movements in their daily lives.